ANALYSIS OF OVERPRESSURE CHARACTERISTIC IN ASI AND ARAM FIELDS, NORTH SUMATRA BASIN, EAST ACEH - Kharisma Taruna, Salwanita
This research was conducted in two fields in North Sumatra Basin, Asi and Aram Fields. This basin is well known for having overpressure zones. Pore pressure analysis is needed to avoid the drilling risks due to overpressure zone, such as blowout, kick, and loss. The purpose of this study are to estimate pore pressure magnitude in the overpressure zone using wireline log, determine the top of overpressure, analyze the overpressure generating mechanism, and analyze the relationship between geological conditions in the study area and overpressure in the study area. This research was performed in two wells (ASI-1 and ASI-2) in Asi Field and one well (ARAM-1) in Aram Field by using wireline log data, well report, temperature data, and pressure data. The results show that the pore pressure is in two conditions, i.e. hydrostatic and overpressure zone with non-loading mechanism. The overpressure zone in the research area starts from a depth of 2111 meters in Asi Field and 2296 meters in Aram field. This overpressure zone is found in Lower Keutapang Formation and reached its peak value in Baong Formation in the claystone interval. The magnitude of pore pressure in the overpressure zone ranges from 2950 – 6592 psi. Overpressure with non-loading mechanism in the study area is estimated to be influenced by clay mineral diagenesis and hydrocarbon maturity.